Accuracy, Acceptability and Readability in the Translation of The Hounds of Baskerville Movie Subtitle - Hanivah, Nurul; Fahrur Rozi; Rahayu Puji Haryanti (English Education Journal, 2024)
The translation of non-academic texts as movie subtitles has its level of complexity, so translation errors often occur. An assessment is needed to maintain the quality of the translation of movie subtitles. Thus, the researchers were interested in investigating the translation quality of movie subtitles by analyzing the level of accuracy, acceptability, and readability in the translation of The Hounds of Baskerville movie subtitles. The study applieda qualitative approach using a descriptive method. The data consisted of English and Indonesian subtitle transcripts of The Hounds of Baskerville movie and the results of the research questionnaire. The research questionnaire was filled by raters whoare a graduate of an English education/English literature study program, and experienced in translating non-fiction texts. This study applied the translation quality assessment model by Nababan (2012). From the results of the assessment of each aspect, a weighting obtained score of 2.2, indicated that the translated text was less accurate, less acceptable, and less readable for the target audience. This finding underscores the importance of balancing those three criteria in a translation. It can encourage those working in the translation and subtitling industry to create subtitles that are accurate, accessible to a wide range of audiences, and culturally relevant.